Melatonin Decreases Pulmonary Vascular Remodeling and Oxygen Sensitivity in Pulmonary Hypertensive Newborn Lambs - Astorga, Cristian R.; González-Candia, Alejandro; Candia, Alejandro A.; Figueroa, Esteban G.; Cañas, Daniel; Ebensperger, Germán; Reyes, Roberto V.; Llanos, Aníbal J.; Herrera, Emilio A. (Frontiers in Physiology, 2018)
Background: Chronic hypoxia and oxidative stress during gestation lead to pulmonary hypertension of the neonate (PHN), a condition characterized by abnormal pulmonary arterial reactivity and remodelling. Melatonin has strong antioxidant properties and improves pulmonary vascular function. Here, we aimed to study the effects of melatonin on the function and structure of pulmonary arteries from PHN lambs. Methods: Twelve lambs (Ovis aries) gestated and born at highlands (3,600 m) were instrumented with systemic and pulmonary catheters. Six of them were assigned to the control group (CN, oral vehicle) and 6 were treated with melatonin (MN, 1 mg.kg-1.d-1) during 10 days. At the end of treatment, we performed a graded oxygenation protocol to assess cardiopulmonary responses to inspired oxygen variations. Further, we obtained lung and pulmonary trunk samples for histology, molecular biology and immunohistochemistry determinations. Results: Melatonin reduced the in vivo pulmonary pressor response to oxygenation changes. In addition, melatonin decreased cellular density of the media and diminished the proliferation marker KI67 in resistance vessels and pulmonary trunk (p<0.05). This was associated with a decreased in the remodelling markers α-actin (CN 1.28±0.18 vs. MN 0.77±0.04, p<0.05) and smoothelin-B (CN 2.13±0.31 vs. MN 0.88±0.27, p<0.05). Further, melatonin increased vascular density by 134% and vascular luminal surface by 173% (p<0.05). Finally, melatonin decreased nitrotyrosine, an oxidative stress marker, in small pulmonary vessels (CN 5.12±0.84 vs. MN 1.14±0.34, p<0.05). Conclusion: Postnatal administration of melatonin blunts the cardiopulmonary response to hypoxia, reduces the pathological vascular remodelling, and increases angiogenesis in pulmonary hypertensive neonatal lambs. These effects improve the pulmonary vascular structure and function in the neonatal period under chronic hypoxia.